Hubungan Antara Biaya Operasional dan Laba Pada PT Telekomunikasi Indonesia Tbk - Dea Alvindha; Agnes Bintang; Manurung, Elizabeth Tiur (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the influence of operational costs on profit before tax at PT Telkom Indonesia Tbk during the 2016–2024 period. Analysis was carried out using quantitative methods with descriptive and associative approaches, as well as simple linear regression techniques. The data used is secondary data originating from the company's official financial reports. The research results show that operational costs have a significant influence on profit before tax, with a regression coefficient of -0.934. This means that every 1 unit increase in operational costs will cause a decrease in profit before tax of 0.934 units. The variability of profit before tax can be explained by operational costs seen from the R square value of 0.895. These findings emphasize the importance of efficient operational cost management to increase company profitability.